A bulk adjusted linear combination of atomic orbitals (BA‐LCAO) approach for nanoparticles. Issue 1 (3rd October 2018) - Kaledin, Alexey L.; Hill, Craig L.; Lian, Tianquan; Musaev, Djamaladdin G.
Abstract : We describe a bulk adjusted linear combination of atomic orbitals (BA‐LCAO) approach for nanoparticles. In this method, we apply a many‐body scaling function (in similar manner as in the environment‐modified total energy based tight‐binding method) to the DFT‐derived diatomic AO interaction potentials (like in the conventional orbital‐based density‐functional tight binding approach) strictly according to atomic valences acquired naturally in a bulk structure. This modification, (a) facilitates all atom orbital‐based electronic structure calculations of charge carrier dynamics in nanoscale structures with a molecular acceptor, and (b) allows to closely match high‐level density functional calculation data (previously adjusted to the available experimental findings) for bulk structures. To advance practical application of the BA‐LCAO approach we parameterize the Hamiltonian of wurtzite CdSe by fitting its band structure to a high‐level DFT reference, corrected for experimentally measured band edges. Here, unlike in conventional DFTB approach, we: (1) use hydrogen‐like AOs for the basis as exact atomic eigenfunctions, while orbital energies of which are taken from experimentally measured ionization potentials, and (2) parameterize the many‐body scaling functions rather than the atomic wavefunctions. Development of this approach and parameters is guided by our goals to devise a method capable of simultaneously treating the problems of ( i ) interfacial electron/hole transfer between finite, variable size nanoparticles and electron scavenging molecules, and ( ii ) high‐energy electronic transitions (Auger transitions) that mediate multi‐exciton decay in quantum dots. Electronic structure results are described for CdSe quantum dots of various sizes. © 2018 Wiley Periodicals, Inc. Abstract : The authors describe a (bulk adjusted) BA‐LCAO method that provides greater flexibility for improving the band structure of nanoparticles. The authors have shown that such key properties as the valence and conduction band edges, crucial in electron/hole transfer processes and consequently the band gap, which also controls Auger assisted electron/hole transfer, can be reproduced exactly for given empirical reference data.